2022
DOI: 10.1021/acsaem.2c00606
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Pulverization of Co-Free Nickel-Rich Cathodes for Improved High-Voltage Cycling of Lithium-Ion Batteries

Abstract: Nickel-rich cathode materials are quickly becoming the next commercial cathode for electric vehicles; however, their long-term cycle life retention and air stability remain a barrier to the use of these lower-cost, higher-energy density materials. Surface reactivity and mechanical degradation, especially at high voltages, remain two issues that impede these material’s commercialization. While surface treatments have shown great promise in reducing surface reactivity, mechanical degradation or “cathode cracking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Previously, it was shown that ball-milling microparticles to morphed oval/ellipse/spherical particles could increase the tap density. 6 The reason is that the spherical shape group of particles tends to occupy more volume, thus increasing the tap density and the system's cathode level energy density. 100 Optimizing any of the mentioned synthesis methods in this work or discovering a new creative synthesis route that can produce spherical nanomaterials can be a potential development toward the commercial pathway for nanomaterials.…”
Section: Future Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Previously, it was shown that ball-milling microparticles to morphed oval/ellipse/spherical particles could increase the tap density. 6 The reason is that the spherical shape group of particles tends to occupy more volume, thus increasing the tap density and the system's cathode level energy density. 100 Optimizing any of the mentioned synthesis methods in this work or discovering a new creative synthesis route that can produce spherical nanomaterials can be a potential development toward the commercial pathway for nanomaterials.…”
Section: Future Significancementioning
confidence: 99%
“…9,77,96,97 Nanomaterials (NM) have the advantage of being grown into a monodisperse, single-crystal morphology from the bottom-up by arranging the atoms perfectly or deconstructing microparticles by applying external energy. 98,99 Researchers can synthesize S.C. materials for cathode materials at higher calcination temperatures utilizing existing precursor morphology. 16,53 This creates a very vague boundary to distinguish N.M. and S.C. materials.…”
Section: Morphological Significance Of Cathode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, efforts are being made towards the understanding the role of Co ions in layered structures (Voronina et al, 2020;Liu et al, 2021d;Gent et al, 2022;Shen et al, 2022a), so that suitable ions for replacement of Co ions may be identified . Considering, abundance and high price of Co (Brow et al, 2022), various research groups around the world are working towards designing Co free Ni rich layered oxide cathode by looking for a suitable ion to replace Co (Mu et 2022;.…”
Section: Co Free Ni Rich Oxidesmentioning
confidence: 99%
“…The useful life of a battery is directly related to its capacity fade (a loss in capacity upon cycling or aging), which can result from several interconnected mechanisms that lead to increased cell resistance, loss of active material, and/or loss of lithium inventory. 4,8,9 In modern LIB technology, capacity fade is partially governed by the dissolution of transition metals inside the cathode. 10,11 This dissolution is caused by an oxidation reaction when the transition metal surface is exposed to hydrofluoric acid (HF).…”
Section: Introductionmentioning
confidence: 99%